The education of the human being in times of planetary crisis. - Roa, Iruxa; Escobar, Juan Fernández; Adúm, Saadda Fatuly; Letechi, Alex Luque; Torres, Carlos Samaniego (Conexiones UG, 2023)
Transcomplex education invites preschool teachers to sensitize so that within these micro worlds of life in current Venezuelan families, they intertwine innovative theories and practices that redefine education from multireferentiality, building knowledge based on the understanding of the reality of the world around her. Facing challenges, imbalances and balances approached in a different way, since from the transcomplexity the biological, psychological, cultural, social, axiological, physical, spiritual, historical and emotional play a preponderant role when studying reality. This educational situation invites a deep reflexivity where transdisciplinarity builds and consolidates a new transparadigm for the understanding and proper management of grief in these times of pandemic, transcending the categories of approaches used so far in these scenarios to learn and teach. The essay presents initial reflections, then educational brushstrokes for the understanding of mourning and affective loss in times of pandemic from transcomplexity, so that a multidiversity of collaborative pedagogical tools is used to cement and strengthen the essence of human existence. Next, the transcomplex transparadigmatic hatching is presented, considering some approaches that facilitate the integral strengthening of boys and girls during their mourning processes in teachers. Close with final thoughts and reflections.